OPTIMALISASI FUNGSI PENGAWASAN DPRD PROVINSI RIAU TERHADAP ALOKASI ANGGARAN PERCEPATAN PENANGANAN PANDEMI COVID-19 MELALUI APBD TAHUN 2020 - M. Dani Eka Wijaya; Mexsasai Indra; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In a democratic country, the existence of a Regional People'sRepresentative Council or referred to as a legislative body is a must. The reasonis that the legislature is the people's representative in making laws or regionalregulations that will be applied to the people. By law the DPRD has the moststrategic position in carrying out the supervisory function of local governments.One of the central council functions is the supervisory function, while the actionsreferred to by the institution are more preventive in nature which impliesevaluating and supervising local government programs. Likewise in RiauProvince, the Riau Provincial DPRD has supervised the use of the budget for theacceleration of the handling of the Covid-19 Panemdi in the 2020 APBD. Asstated in the explanation of Article 41 of Law Number 32 of 2014 concerningRegional Government, it states that